Chas. Ben. Darwin, Ordinances of the City of Burlington 72-73 (1847) - (:unkn) unknown (My University, 1847)
§§ 1-4: Prohibited any merchant, trader, or other person to retail or deliver gun powder during the night. Violators fined five dollars. Gun powder limited to twenty-five pounds and only in a "safe canister." Gun powder shall only be kept in dwellings approved by the Council. Violators fined one hundred dollars, with the powder confiscated with cost.
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION